Clear Cell Variant of Solid Pseudopapillary Neoplasm of the Pancreas: A Report of a Rare Variant and Review of the Literature. (August 2019) - Costales, Cristina; Mehta, Arjun; Kulkarni, Sujit; Larson, Brent K.
The clear cell variant of solid pseudopapillary neoplasm (ccSPN) of the pancreas was first described in 2006. In this article, we report a case of this rare variant and review the few published reports. Both the current and previous reports show that ccSPN has several morphologic differences from conventional SPN, including clear vacuoles, fewer pseudopapillary formations, more solid/diffuse architecture, less hemorrhage, and fewer cholesterol clefts. Some of these features peculiar to ccSPN, such as solid/diffuse architecture, have been proposed to suggest aggressive behavior, though reports of ccSPN are rare and often have limited clinical follow-up. ccSPN also appears to occur more frequently in males than conventional SPNs. These clinical and pathologic features lead to unique set of differential diagnostic considerations for ccSPN, including metastatic renal cell carcinoma, perivascular epithelial cell tumor, and clear cell variants of other carcinomas. These unique features, atypical differential, and uncertain prognostic ramifications all make ccSPN an important variant to be aware of and report.